2017
DOI: 10.1093/neuros/nyw169
|View full text |Cite
|
Sign up to set email alerts
|

Resection of Navigated Transcranial Magnetic Stimulation-Positive Prerolandic Motor Areas Causes Permanent Impairment of Motor Function

Abstract: After resection of nTMS-positive motor points, 62% of patients suffered from a new permanent paresis. Thus, even though they are located in the superior or middle frontal gyrus, these cortical areas must undergo intraoperative mapping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…Indeed, the extent and exact spatial location of motor representations are not fixed and have shown to be subject to a high degree of plasticity and inter-individual differences in presence of brain tumors [49][50][51][52][53]. Further, previous work has shown that true motor-positive spots belonging to the primary motor representations can extent far anteriorly into the suspected supplementary motor areas [54]. Thus, more widespread patterns of motor-positive points as mapped out by pp-nTMS, reaching even beyond the borders of the precentral gyrus, seem possible and need to be considered for further validation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the extent and exact spatial location of motor representations are not fixed and have shown to be subject to a high degree of plasticity and inter-individual differences in presence of brain tumors [49][50][51][52][53]. Further, previous work has shown that true motor-positive spots belonging to the primary motor representations can extent far anteriorly into the suspected supplementary motor areas [54]. Thus, more widespread patterns of motor-positive points as mapped out by pp-nTMS, reaching even beyond the borders of the precentral gyrus, seem possible and need to be considered for further validation.…”
Section: Discussionmentioning
confidence: 99%
“…This was done to ensure that induced motor impairment during SMA mapping could be attributed to SMA stimulation without being confounded by possible stimulation of very anterior parts of primary motor cortex representations 36,65,66 . Prior reports have indicated that the primary motor cortex can extend far anteriorly and beyond the precentral gyrus, with resection of very anterior motor-positive stimulation spots causing postoperative motor deficits related to the primary motor cortex 65 . The number of targets was chosen to allow for complete extension over the anatomical region corresponding to the SMA, while at the same time remaining far enough apart to allow for allocation of effects to each specific target (without presumed stimulation overlap).…”
Section: Methodsmentioning
confidence: 99%
“…This could occur due to the fact that currents perpendicular to the sulcal wall of the precentral gyrus more strongly activate pyramidal neurons in the cortical sheet as compared to currents flowing parallel to the sulcal wall [28]. Studies investigating direct cortical stimulation (DCS) and navigated TMS have shown that stimulation of the premotor cortex can indeed induce motor activity [11] [29]. Unfortunately, both studies only used a PAinduced current direction during TMS motor mapping, which precluded a comparison with LM-induced current.…”
Section: Pa-and Lm-induced Currents Identify Different Mep Motor Mapsmentioning
confidence: 99%
“…In this way, TMS has been shown to be able to identify significantly separated motor area centers for different muscles in the upper extremity [4]. Neuronavigated TMS (nTMS) can potentially be of value in the preparation of neurosurgical interventions in the vicinity of the primary motor cortex, or to monitor changes in the primary motor cortex during the course of rehabilitation (of motor function) after stroke [5]- [11].…”
Section: Introductionmentioning
confidence: 99%